Pembuatan telur asin itik berlapis di Universiti Pendidikan Sultan Idris (UPSI) Malaysia: Manufacturing of coated salted duck eggs at the Sultan Idris Education University (UPSI) Malaysia - Sugiarti, Sugiarti; Rostini , Tintin; Jaelani , Achmad; Fitriani, Fitriani; Hidayatullah, Hidayatullah; Harun , Makmur; K, Anna Permatasari (Fakultas Peternakan Universitas Papua, 2025)
ABSTRACT This community service program aimed to enhance the skills of academic participants in producing Itik Alabio salted eggs using the paste method, while introducing the product as part of the South Kalimantan genetic resource (plasma nutfah) to the international academic community. The activity was carried out at Universiti Pendidikan Sultan Idris (UPSI), Malaysia, involving participants from various higher education institutions. The methods used included lectures, technical demonstrations, and hands-on practice. The results showed an increase in participant understanding, from 63% in the pre-test to 80% in the post-test. The final product demonstrated good quality, with a firm texture, reddish-yellow yolk, and a distinct savory flavor. This program highlights the effectiveness of cross-border participatory training in promoting local food products and transferring simple, applicable food processing technologies. Keywords: Food technology; International community service; Itik Alabio; Salted egg; UPSI ABSTRAK Program pengabdian ini bertujuan untuk meningkatkan keterampilan civitas akademika dalam pembuatan telur asin Itik Alabio dengan metode pasta, sekaligus memperkenalkan produk tersebut sebagai bagian dari plasma nutfah Kalimantan Selatan kepada komunitas akademik internasional. Kegiatan dilaksanakan di Universiti Pendidikan Sultan Idris (UPSI) Malaysia, dengan peserta dari berbagai institusi pendidikan tinggi. Metode yang digunakan meliputi penyuluhan, demonstrasi teknis, dan praktik langsung. Hasil menunjukkan peningkatan pemahaman peserta dari 63% menjadi 80%. Produk akhir memiliki kualitas baik, dengan tekstur padat, warna kuning kemerahan, dan rasa gurih khas. Kegiatan ini menunjukkan efektivitas metode pelatihan partisipatif lintas negara dalam promosi pangan lokal dan transfer teknologi sederhana yang aplikatif. Kata kunci: Itik Alabio; Pengabdian internasional; Teknologi pangan; Telur asin; UPSI